1998
DOI: 10.1103/physrevlett.81.2276
|View full text |Cite
|
Sign up to set email alerts
|

Two Length Scales and Crossover Behavior in the Critical Diffuse Scattering fromV2H

Abstract: We have observed two length scales in a V 2 H crystal above the b 1 -b 2 phase transition. A sharp Lorentzian profile in the critical diffuse scattering was superimposed on a broader one for a low-energy x-ray experiment in reflection, while no sharp component appeared in transmission at high energy. For the sharp component, we extracted tricritical exponents n 1 and g 1 at small reduced temperatures t, where fluctuations are coherent over large distances. For larger t, where the correlation length is comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 23 publications
2
20
1
Order By: Relevance
“…Systematic studies of many materials in which twolength-scale behavior has been found, [6][7][8][9][10][11][12][13][14][15][16] including previous studies of V 2 H, 4 have concluded that the narrow central peak of the CDS only occurs in the scattering from a defective "skin layer," that is a region of the material that starts a few hundred angstrom below the surface and extends several tens of micrometer below the surface. However, to the best of our knowledge, the two-length-scale behavior in V 2 H is different from that which has been observed in any other material, because in V 2 H the phase transition in the bulk is a firstorder transition.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Systematic studies of many materials in which twolength-scale behavior has been found, [6][7][8][9][10][11][12][13][14][15][16] including previous studies of V 2 H, 4 have concluded that the narrow central peak of the CDS only occurs in the scattering from a defective "skin layer," that is a region of the material that starts a few hundred angstrom below the surface and extends several tens of micrometer below the surface. However, to the best of our knowledge, the two-length-scale behavior in V 2 H is different from that which has been observed in any other material, because in V 2 H the phase transition in the bulk is a firstorder transition.…”
Section: Introductionmentioning
confidence: 98%
“…However, to the best of our knowledge, the two-length-scale behavior in V 2 H is different from that which has been observed in any other material, because in V 2 H the phase transition in the bulk is a firstorder transition. In the skin layer, instead, the ordering is more complicated as found experimentally by a number of unusual phenomena including: ͑1͒ diffuse scattering which, as the temperature is lowered toward a critical value, consists of a broad peak that changes only slightly with temperature and a narrow central peak with an amplitude that diverges; 4 ͑2͒ an effective critical temperature T c ͑y͒ for the behavior of the central peak that changes with the depth y below the surface and extrapolates to a temperature T c ϱ that always exceeds the bulk transition temperature T 0 ; 5 ͑3͒ a crossover in the universal critical behavior shown by the central peak from three-dimensional mean-field critical behavior to a different universality class as the temperature increases from T c ͑y͒; 4,5 ͑4͒ a narrow two-phase region and a weak first-order transition observed at temperatures T 0 ͑y͒ slightly below the critical value. 17 In order to explain these experimental findings we present a theory which accounts for the distribution of defects experimentally detected: 3 edge dislocations occur mostly in the skin layer, accumulating near the surface; they are arranged in arrays of parallel lines which we refer to as "walls;" each wall consists of lines that are oriented in either of the two directions parallel to the surface; the walls extend into the crystal and are thus oriented in either of the two directions perpendicular to the surface.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such studies can be regarded as a systematic exploration of the effects of point defects on the CuGeO 3 structural phase transition. Thus, as a byproduct of our Cu 1−x (Zn,Mg) x GeO 3 phase diagram studies, we also are able to test the hypothesis that the long length scale fluctuations are caused by point defects 10 . Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, even if the idea that the second length scale originates from defects is taken for granted, there exists additional complexity because the defects can either be point defects or line defects such as dislocations. A recent study suggests that point defects are responsible for the occurrence of the second length scale 10 . The dislocation theory, on the other hand, has been less favored.…”
Section: Discussionmentioning
confidence: 99%